Power Dynamics in Music: Creative Power - Bedirhan Büyükduman; Emine Ceylan Ünal Akbulut (Konservatoryum)
This study, prepared with the assumption that the concept of power, which seems to be exclusively within the domain of political science, is omnipresent, aims to evaluate the elements of the creative power of the composer, considered the first step of the power dynamics within music, the most abstract of the arts. Document analysis was used as the data collection tool, and the data obtained were summarized and interpreted using descriptive analysis. The study, designed with a generating-theory pattern, is limited to the intrinsic power of music and the notions of creative power. First, the intrinsic power of music, which exists due to its significance for powers, is explained to contextualize the importance of music for powers; subsequently, the notion of creative power among the internal power dynamics is elucidated. The conclusion of the article reveals that creative power, attributed a divine status, has the capability to support or undermine political power in matters such as determining or changing culture—due to its ability to influence masses. It is concluded that creative power consolidates and perpetuates its authority by operating a mechanism of consent created through dynamics such as performers, orchestras, conductors, and political power for the manifestation of its power. Additionally, it continuously reminds its dominance and authority by creating the illusion of freedom among its subjects.